ELEVATING LEARNING: DEVELOPING HOTS CHALLENGES FOR SENIOR STUDENTS AT SMK PUI CIKIJING - Sifa Nurfauziyah; Ida Hamidah; Sun Suntini; Fahrus Zaman Fadhly (Indonesian Journal of Learning and Instruction, 2024)
This study aims to develop Higher Order Thinking Skills (HOTS) questions for Class XII Indonesian at SMK PUI Cikijing based on four HOTS criteria: the Operational Verb (KKO) aspect, critical thinking skills, creative thinking, and problem-solving. The research method used in this study is Research and Development (R&D). The development model employed is the 4D model, limited to development only. Hence, the development stage begins with defining (analyzing Indonesian HOTS questions), designing (formulating HOTS questions based on the analysis of HOTS items regarding KKO aspects, critical thinking skills, creative thinking, and problem-solving), and developing (creating HOTS questions based on the analysis of HOTS questions in terms of KKO aspects, critical thinking skills, creative thinking, and problem-solving). Based on the analysis of the profile of Indonesian HOTS questions for Class XII at SMK PUI Cikijing, it is found that they are lacking in fulfilling the criteria for HOTS questions. Only 6% or 2 items are identified as HOTS questions, 30% or 9 questions need improvement, and 63% or 19 questions do not meet the HOTS criteria. Thus, there is a need to design HOTS questions based on the analysis of the HOTS item profile conducted in the defining stage. Subsequently, Low-Order Thinking Skills (LOTS) questions are transformed into HOTS questions based on four HOTS criteria: the Operational Verb (KKO) aspects, including C4 (analyzing) and C5 (evaluating) cognitive domains, critical thinking skills, creative thinking, and problem-solving. Keywords: development of HOTS questions, HOTS criteria, KKO, critical thinking skills, creative thinking skills, problem-solving skills.